THE NATION’S HUMAN CAPITAL IS A MAJOR RESOURCE OF THE STATE’S INNOVATION POTENTIAL - Bogashko, Aleksander (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The problem is important and relevant because in the process of formation of the world economy and economic science, the goals and objectives, means and criteria of modern socio-economic development of countries have been rethought. Studies of competitiveness, priority factors of economic growth, and criteria for the effectiveness of economic activity in a market environment have become relevant. The state of the economy, intensification, progress of economic development depend on innovative potential and human capital, which affect the system of economic relations at the micro, macro and mega levels. The aim of the article is to study the evolution of the scientific concept of human capital and determine the socio-economic nature of national human capital. The article also determines the value of human capital in the system of factors of innovative development of the economy of countries. The article used general scientific and special research methods: analysis and synthesis, morphological analysis, logical generalization and comparison, graphical method.The study presents approaches to determining the socio-economic category of “human capital”. An analysis of the scientific literature indicates that the category of “human capital” most fully reflects the role and place of people in the economic system.The article notes that different countries of the world use different indicators of human capital: the Human Development Index, the Quality of Life Index and the Index of Human Happiness. The most common indicator of human capital development is the Human Development Index. The article presents the author's classification of human capital, which includes the levels and structure of capital. This will help government agencies better regulate the development of national human capital.